THEORETICAL ANALYSIS OF THE PROBLEM OF FORMING THE RESPONSIBLE ATTITUDE TO HEALTH IN CHILDREN AND YOUTH (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article is devoted to consideration of the actual problem of formation of a healthy way of life of children of modern youth. An overview of the basic theoretical and conceptual foundations on this issue is carried out. Special attention is paid to the retrospective analysis of the problem of creating the healthy lifestyle culture, the value-based attitude towards person's health. It is given grounds for the necessity of the complexity of the process of creation of the responsible attitude towards personal health of modern youth which is aimed at developing of the personal viewpoint of a person towards his/her own health. It has also been proven that the perspective of improving the health of young people is correlated with systemic activities of the creation of the healthy lifestyle and it is much more effective and cost-effective strategy than the constant increase of the cost for the treatment of the consequences of the unhealthy lifestyle.Therefore, the main content of the activity of all educational institutions in creating the responsible attitude towards personal health of modern youth is in our opinion, the development and implementation of social projects based on certain preconditions, principles, tasks, strategies, mechanisms determined by the creation of the responsible attitude towards health, and have as a purpose - improvement of the health of this particular category of children, and the general population as a whole. The most relevant focal areas in the development and implementation of all programs relating to the creation of healthy lifestyle of young people are the following: proper training of specialists, support of youth initiatives, monitoring of the situation and effectiveness of the projects, spreading and improvement of information and education programs, combining the efforts of various ministries, committees and non-governmental organizations, etc.All in all, health is a complex, multidimensional phenomenon that has a heterogeneous structure that combines a variety of components and reflects the fundamental aspects of human existence.
Keywords: health, youth, responsible attitude, children, young, formation, problem.